Teaching ‘Correct’ Attitudes: an Anglican Emissary to Sweden and Finland in 1944 - Ketola, Hanna-Maija (The journal of ecclesiastical history, 2004)
In autumn 1944, the British Ministry of Information sent one of its officials, the Revd Herbert M. Waddams, to Sweden and Finland. His task was to collect information about opinions in church circles in both countries and to try to persuade them to a more favourable attitude towards the Allies, especially the Soviet Union. Sweden had remained neutral throughout the war and Finland had just made peace with the Allies. Waddams's memoranda on the trip reveal how the assessment of the international situation by a representative of a British government ministry differed from that of churchmen in Sweden and Finland.